Researching Newspaper Photographs: Revealing The Prevailing Paradigms - Samani, Mus Chairil (Jurnal Pengajian Media Malaysia, 2005)
Photographs play a dominant role in newspaper reporting of current affairs. As a news item, a photograph complements the written word. Where the accompanying news story is missing, the caption elaborates on the essence of the photograph. A review of the dominant journals in media and communication studies will indicate that research on photographs has been somewhat limited. The lack of published research on newspapers’ photographs should not be misconstrued as a lack of interest among researchers to study this phenomenon. This paper seeks to communicate the contrasting research methodologies employed by researchers in studying newspaper photographs. The findings indicate two dominant paradigms in studying the various photographs published by newspaper: positivism and interpretative. The positivism paradigm reduces photographs into categories and quantifiable numbers to account for the amount of images printed in the pages of a newspaper. Images of importance are those that can be observed, measured and quantified. The interpretative paradigm looks at photograph within the dichotomy of nature and culture.